Mating patterns and post-mating isolation in three cryptic species of the Engystomops petersi species complex - Trillo P.A. (2017)
This research was funded by a National Science Foundation IOS-0940466 grant to KH and a UNESCO-L’Oreal-CONCYTEC 001-2009-L’Oreal fellowship to PAT. Laboratory work was funded by grants from the Secretar?´a de Educacio´n Superior, Ciencia, Tecnolog?´a e Innovación (SENESCYT, Arca de Noe´ Initiative) and a Pontificia Universidad Católica del Ecuador (PUCE-DGA) grant to SRR. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.